Determinants of Work-Related Stress among Staff Nurses in Inpatient Wards at Al Huda Hospital - Hadani, Kilmatuna; Mayasari, Ema; Yudhana, Amarin; Sari, Reny Mareta (Universitas STRADA Indonesia, 2025)
Work-related stress among nurses is predicted to continue increasing in the coming years. This condition represents a growing concern because it is closely related to nurses’ health and safety as well as the quality of healthcare services. Therefore, this research aim to analyze factors that may influence work-related stress, including workload, work shifts, and marital status. This study employed a quantitative approach using a cross-sectional design. The respondents consisted of 60 staff nurses working in inpatient wards at Al Huda Hospital, Banyuwangi, who were selected using accidental sampling. Data were collected using structured questionnaires and analyzed using ordinal logistic regression. The results showed that 27 respondents (45.0%) experienced high work-related stress, 26 respondents (43.3%) moderate stress, and 7 respondents (11.7%) low stress. Statistical analysis indicated that workload (p = 0.773), work shift (p = 0.228), and marital status (p = 0.794) did not have a significant effect on nurses’ work-related stress (p > 0.05). Workload, work shift, and marital status were not significantly associated with work-related stress among nurses.